Battery-free, wireless sensors for full-body pressure and temperature mapping - Han, Seungyong; Kim, Jeonghyun; Won, Sang Min; Ma, Yinji; Kang, Daeshik; Xie, Zhaoqian; Lee, Kyu Tae; Chung, Ha Uk; Banks, Anthony; Min, Seunghwan; Heo, Seung Yun; Davies, Charles R.; et al. (Science Translational Medicine, 2018)
Thin, soft, skin-like sensors capable of precise, continuous measurements of physiological health have broad potential relevance to clinical health care. Use of sensors distributed over a wide area for full-body, spatiotemporal mapping of physiological processes would be a considerable advance for this field. We introduce materials, device designs, wireless power delivery and communication strategies, and overall system architectures for skin-like, battery-free sensors of temperature and pressure that can be used across the entire body. Combined experimental and theoretical investigations of the sensor operation and the modes for wireless addressing define the key features of these systems. Studies with human subjects in clinical sleep laboratories and in adjustable hospital beds demonstrate functionality of the sensors, with potential implications for monitoring of circadian cycles and mitigating risks for pressure-induced skin ulcers.
Keywords: Biosensing Techniques; Equipment Design; Humans; Pressure; Skin; Temperature; Thermography; Wireless Technology